Pan Trinbago Gets More Trincity Land - Unknown (Newsday)
Pan Trinbago president Patrick Arnold confirmed that his organisation received a letter of approval from Minister in the Ministry of Finance Christine Sahadeo, for an additional 3 acres of land. Arnold said that his organisation applied for a further three acres of land before 2000, given the magnitude of its Trincity project where the Pan Headquarters will be relocated. Added to the headquarters a chroming factory among and other projects is also earmarked for the site.
Keywords: Steel bands (Music) -- Administration -- Trinidad and Tobago; Land tenure -- Trinidad and Tobago; Pan Trinbago (Organization) -- Headquarters